2011
DOI: 10.1017/s1041610211002171
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of gray matter atrophy in dementia with Lewy bodies: a voxel-based morphometry study

Abstract: DLB is associated with less gray matter atrophy and relative preservation of the medial temporal lobe when compared to AD. Degree of medial temporal atrophy may be a useful imaging biomarker and our results provide support for its inclusion in the revised consensus criteria for DLB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
61
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 58 publications
(74 citation statements)
references
References 33 publications
11
61
0
2
Order By: Relevance
“…We have previously reported the patterns of gray matter atrophy in this group 12 and found very few areas of significant volume loss in DLB when compared to controls. Interestingly, there was a trend toward a posterior pattern of atrophy in DLB, although this did not reach statistical significance.…”
Section: Subject Demographicsmentioning
confidence: 60%
See 2 more Smart Citations
“…We have previously reported the patterns of gray matter atrophy in this group 12 and found very few areas of significant volume loss in DLB when compared to controls. Interestingly, there was a trend toward a posterior pattern of atrophy in DLB, although this did not reach statistical significance.…”
Section: Subject Demographicsmentioning
confidence: 60%
“…All subjects underwent clinical and neuropsychological evaluations with diagnostic procedures previously employed by our group. 12 Thirtyfive control subjects were recruited from among relatives and friends of subjects with dementia or volunteered via advertisements in local community newsletters.…”
Section: Methods Subject Recruitment and Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Hippocampal AD pathology is also a feature of DLB, as previous imaging studies have consistently demonstrated that the level of hippocampal atrophy observed in DLB is less than in AD (Hashimoto et al, 1998; Tam et al, 2005; Burton et al, 2009; Watson et al, 2012), and the level of atrophy relates to concurrent AD pathology measured post mortem (Burton et al, 2009; Kantarci et al, 2012). The extent of the atrophy may also influence the subsequent clinical course of DLB, as individuals with higher levels of hippocampal atrophy have a shorter survival time compared with those with lower levels of atrophy (Graff‐Radford et al, 2016).…”
Section: Introductionmentioning
confidence: 96%
“…In the 2011 awards, the second and third place winning papers by Allan et al (2012) and Watson et al (2012) dealt respectively with white matter change in late life depression and gray matter changes in Dementia with Lewy bodies (DLB). Indeed, the paper of Taylor et al (2013) is the second DLB imaging paper from Newcastle-upon-Tyne to win an award in two consecutive award rounds.…”
mentioning
confidence: 99%